Soccer related sudden deaths in Turkey - Özdemir, C.; Saka, T.; Asil, H.; Üzün, I.; Öner, M. (Journal of Sports Science & Medicine, 2008)
Regular physical exercise is recommended by the medical community, because it offers the potential to reduce the incidence of coronary events. On the other hand, vigorous exertion may act as a trigger of acute myocardial infarction and sudden cardiac death in susceptible individuals. Death during sports activities differs among sports disciplines and countries. In Turkey, soccer attracts more spectators than any other sports activity and the attention of the press and media, and is preferred over other sports by many young and middle-aged individuals. As autopsy-based studies are infrequent in literature and there is a lack of data detailing sudden death during physical activity in Turkey, we present a Turkish series of sudden deaths that occurred during soccer games based on data provided by the Morgue Specialization Department of the Council of Forensic Medicine. We identified 15 male cases of soccer-related sudden death aged from 10 to 48 years. Coronary artery disease was identified as the cause of sudden death in 11 cases.